A regime switching analysis of Indonesia's exchange market pressure - Unggul Heriqbaldi, Dr. (World Scientific Publishing Co. Pte Ltd., 2014)
This paper examines the extent to which the Indonesia's currency crisis can be accounted for by macro and micro economic fundamentals by employing Markov-switching approach under cross-generation crisis models. In order to represent the speculative attack in the economy, the study utilized one of the measures that is most widely adopted to signal the breakup of a crisis, the Exchange Market Pressure Index (EMPI). This paper found the following. First, liquidity (DC), real exchange rate (RER2) and ratio of banking credit to GDP (BCred) were found to significantly influence the EMPI, indicating that the behavior of EMPI has the characteristic that is predicted by the first, second, and third generation of crisis model found to significantly influence the EMPI, indicating that the behavior of EMPI has the characteristic that is predicted by the first, second and third generation of crisis models. Second, the LR test showed that regime switching dynamic model is more robust than ordinary dynamic model in explaining the EMPI, suggesting that speculative attacks tend to have the characteristics of multiple equilibria. Third, the transition probability matrix results showed that the tranquility regime was more persistent than the volatile regime.